2011
DOI: 10.1021/ef200136w
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sulfate for Water Based Enhanced Oil Recovery during Spontaneous Imbibition in Chalk

Abstract: The effect of increased sulfate concentration in the imbibing water during oil recovery by spontaneous imbibitions in different outcrop chalks at various wettability conditions at 130 °C has been determined. Core plugs from three chalk outcrops, Rørdal, Niobrara, and Stevns, were aged in crude oil and included in this study. Stevns chalk exhibited increased oil recovery during spontaneous imbibition with increased concentration of sulfate in the imbibing water phase. The effect was less than reported by others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…In the former case, connate water should be continuous, whereas, in the latter, it can be a discontinuous phase. Oil-wetness was, as described previously, established by silane modification according to the methodology of Grate et al (2013). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the former case, connate water should be continuous, whereas, in the latter, it can be a discontinuous phase. Oil-wetness was, as described previously, established by silane modification according to the methodology of Grate et al (2013). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Micromodels were rendered oil-wet with a slight modification of the procedure described by Grate et al (2013). The models were dried under nitrogen flow and filled with concentrated nitric acid with a syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that PDIs become more effective as temperature increases through contact angle measurements on a calcite surface modified with oil and long-chain fatty acids, as reported by Tweheyo et al (2006) and Gomari et al (2006). Fernø et al (2011) concluded that different carbonate rocks may have different responses to the same brine composition. The authors studied the effect of sulfate concentration on oil recovery during spontaneous imbibition in different outcrop chalks (Stevns Klint, Rørdal and Niobrara).…”
Section: Effect Of Brine Salinity and Composition On Oil Recoverymentioning
confidence: 99%
“…Increasing the sulfate concentration in seawater resulted in more change of wettability towards water-wetness. Ferno et al (2011) performed spontaneous imbibition tests on different chalk outcrops (Stevns, Rordal, and Niobrara) using brines with and without sulfate. The effect of adding sulfate to the brines on wettability alteration was observed only in plugs from Stevns Klint chalk, but not from the other 2 chalk types.…”
Section: Introductionmentioning
confidence: 99%